RETURN SAHAM MELALUI PROFITABILITAS SEBAGAI VARIABEL INTERVENING: LIKUIDITAS DAN STRUKTUR MODAL - Yeni, Fitri; Khair, Miftahul; Putri, Nabila Ulfa Maharani (Universitas Muhammadiyah Palembang, 2024)
This research aims to assess the role of profitability in mediating the impact of liquidity and capital structure on stock returns in food and beverage companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The study population included 29 companies, and the sample taken was 26 companies using purposive sampling method. The results show that there is a significant positive correlation between liquidity and profitability, while capital structure has no impact on profitability. In addition, liquidity, capital structure, and profitability are significantly negatively correlated with stock returns. Profitability also does not function as a mediator in the relationship between liquidity, capital structure and stock returns.